Surviving HIV/AIDS in the inner city : how resourceful Latinas beat the odds - Chase, Sabrina Marie (Studies in medical anthropology., 2011)
Surviving HIV/AIDS in the Inner City explores the survival strategies of poor, HIV-positive Puerto Rican women by asking four key questions: Given their limited resources, how did they manage an illness as serious as HIV/AIDS? Did they look for alternatives to conventional medical treatment? Did the challenges they faced deprive them of self-determination, or could they help themselves and each other? What can we learn from these resourceful women? Through an exploration of life and death among these resourceful women, the book provides the groundwork for inciting positive change in the U.S.